2021
DOI: 10.1038/s41598-021-87891-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from dHL-60 cells as delivery vehicles for diverse therapeutics

Abstract: Extracellular vesicles (EVs) are membrane-derived heterogeneous vesicles that mediate intercellular communications. They have recently been considered as ideal vehicles for drug-delivery systems, and immune cells are suggested as a potential source for drug-loaded EVs. In this study, we investigated the possibility of neutrophils as a source for drug-loaded EVs. Neutrophil-like differentiated human promyelocytic leukemia cells (dHL-60) produced massive amounts of EVs within 1 h. The dHL-60 cells are also easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The recipient cells showed the highest GFP fluorescence. 40 This indicated that the EVs produced from dHL-60 cells could be a potential source for CRISPR/Cas9 RNP delivery. Besides, various engineering technologies have been developed to increase loading efficiency.…”
Section: Delivery Of Crispr/cas9 Rnps By Evsmentioning
confidence: 98%
“…The recipient cells showed the highest GFP fluorescence. 40 This indicated that the EVs produced from dHL-60 cells could be a potential source for CRISPR/Cas9 RNP delivery. Besides, various engineering technologies have been developed to increase loading efficiency.…”
Section: Delivery Of Crispr/cas9 Rnps By Evsmentioning
confidence: 98%
“…Dendritic cells (DCs), Mϕ, and neutrophils, including neutrophil-like promyelocytic cells, are increasingly recognized for their contributory roles in this context. DC-derived EVs, pivotal in the orchestration of immune responses, also partake in antigen presentation, a function that might be exploitable for disease-modifying strategies in NDDs [137][138][139]. Of particular interest are EVs from immature DCs, which are proficient in the release of EVs devoid of T-cell costimulatory molecules, such as major histocompatibility complex class II (MHC-II), thereby proffering an immunologically quiescent profile for therapeutic purposes [140].…”
Section: Biogenesis Of Therapeutically Competent Evs: Potential Cellu...mentioning
confidence: 99%
“…Monocytes and Mϕ represent another cadre of cellular factories, capable of generating EVs that can elude the reticuloendothelial system, thereby circumventing one of the major barriers to effective drug delivery [138]. Such an attribute not only enhances the direct transport of therapeutic cargoes to targeted cells but also augments the therapeutic index of encapsulated drugs [139].…”
Section: Biogenesis Of Therapeutically Competent Evs: Potential Cellu...mentioning
confidence: 99%
“…The dHL-60 cell-derived EVs had higher effector functions (larger amounts and higher efficiencies), higher efficiency of EVs production, and lower immunogenicity than HL-60-derived EVs and neutrophil-derived extracellular vesicles (NDEVs). This suggests that neutrophils and neutrophillike promyelocytic cells could serve as a platform for EVs drug-loading [112]. Qiu et al developed an MSC-derived exosome (MSC-EXO) vector to deliver the cabazitaxel/ tumor necrosis factor-related apoptosis-inducing ligand (CTX/TRAIL) combination via transfection and achieved excellent antitumor activity.…”
Section: Pre-loadingmentioning
confidence: 99%